Cover Image. Issue 3 (24th April 2019) - Brightwell, Camille R.; Markofski, Melissa M.; Moro, Tatiana; Fry, Christopher S.; Porter, Craig; Volpi, Elena; Rasmussen, Blake B.
Abstract : The cover image is based on the Original Article Moderate‐intensity aerobic exercise improves skeletal muscle quality in older adults by Camille R. Brightwell et al., DOI:10.1002/tsm2.70